Main Factors Affecting Decision Making Preferences of Online Versus Traditional Retail in Apparel Industry in India - Bhansali, Chetan (2017)
Abstract Purpose: The chief purpose of the research is to examine the shift in the consumer decision-making process in the Indian apparel industry by exploring factors which are primarily responsible for changing consumer preferences; with transition from traditional retailing methods to online apparel retailers. Design/Methodology/Approach: In this research study, quantitative method is applied for investigating the research domain. Positivism philosophy is implemented with the deductive approach for evaluating shift in the decision-making process with the transition from brick and mortar to online retail stores in Indian apparel industry. The survey is conducted with 67 Indian consumers for collecting relevant data addressing research aim. The data collected is analysed by factor analysis with SPSS measure for performing data deduction while regression analysis is conducted to determine the relationship between key variables related to factors affecting decision making of consumers. Findings: The key findings illustrate that with the transition from traditional retail store to online retail in Indian apparel industry, the decision-making preferences of consumers have also changed. Majority of the Indian consumers prefer online shopping, especially for apparel products. The alterations in demographic, socio-economic and socio-psychological factors are driving the shift towards online shopping. Discount, attractive offers and peer reviews with improved shopping experiences are prime reasons for which more and more consumers are getting attracted to online stores. Availability of wide range of products, comparison of prices and other traits of products, convenience factor and cost advantage also induce consumers to purchase apparel products online. They consider online shopping more reliable over traditional means due to certain aspects such as cash on delivery option, easy refund, reviews, guarantees and legal certification. Implications: The research work will be helpful for new entrants in Indian apparel industry as it contains substantial information about factors influencing the decision-making process of consumers which can be considered for formulating a more effective marketing plan and designing appealing marketing strategies. It will also help existing retailers in Indian apparel segment to understand current scenario of the industry along with trends and challenges. Limitations: The research has focused only on India for studying the changes in consumer buying patterns which has the limited scope of the study. Keywords: Indian apparel industry, consumers, factors, decision-making process, online retail